Improving The Students’ Writing Ability Trhough Mind Mapping Method - Pogaru, Mismar M (Universitas Islam Negeri Palopo, 2025)
The objective of the research was to find out whether the use of mind mapping can improve the students’ writing ability. The researcher applied a pre-experimental method with distributing the online form Questioner that has been adapted. The subject of the research was the English students of master’s degree in State Makassar University academic year 2021/2022. The sample consisted of 26 students of Class D21. The data were collected through distributing the Questionnaire to find out the effectiveness of mind mapping method in improving writing ability, the researcher applied qualitative research. The research result indicated that there was a significant improvement of students’ writing ability.